THE EFFECT OF CAPITAL ADEQUACY RATIO AND OPERATING INCOME OPERATING EXPENSES ON RETURN ON ASSETS IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ade Fauji; Wanda Oktafiani (SEAN Institute, 2022)
This study aims to determine the effect of Capital Adequacy Ratio and Operating Expenses operating income on Return On Assets. The research method used is a quantitative descriptive method, a population of 43 banking companies listed on the Indonesia Stock Exchange for the 2017-2020 period, sampling techniques using purposive sampling so that a sample of 10 companies was obtained. Based on hypothesis testing, the t-test of the CAR of the calculated t value > to the table (2.660 > 1.686) with a significant degree (0.011<0.05), meaning that there is a partial influence between the CAR and the Return On Asset. Meanwhile, Operating Expenses of Operating Income have a calculated value>tof the table (-13,151 > -1,686) with a significant level (0.000 < 0.05). meaning that BOPO partially affects the Return On Asset. and the calculated f value > table (120.260 > 2.86), with a significance value of 0.000 < 0.05, meaning that there is a significant influence between CAR and BOPO together on Return On Assets. The conclusion in this study is that the capital Adequacy ratio partially affects return on assets, BOPO partially affects return on assets, and simultaneously CAR and BOPO affected ct return on assets,